Ethnobotanical Study of Ferns as Traditional Medicine in Central Siberut, Mentawai Island - Syafni, Nova; Bakhtiar, Amri (Universitas Andalas, 2022)
West Sumatra Province has two ethnicities, namely Minangkabau and Mentawai. Both ethnicities have the capability to apply plants in folk medicine. This ethnobotanical study was conducted in Saibi Simokop village in three hamlets namely Sirisurak, Simoilaklak, and Saibi. The study was focused on the use of ferns in traditional medicine. Data collection was carried out using the snowball sampling method to seek the traditional healers (sikerei). The results showed that seven species of ferns were used for treatment of fever, inflammation, and poisoning. The ferns were included Cephalomanes javanicum (Blume) Bosch, Angiopteris evecta (G. Forst.) Hoffm., Dicranopteris linearis (Burm. F.) Underw., Diplazium esculentum (Retz.) Sw., Phymatosorus membranifolium (R. Br.) S.G. Lu, Lecanopteris sp., and Asplenium nidus L. The application of ferns in concoctions was administered topically and some were combined with oral administration.